Optimal tariffs and firm technology choice: An environmental approach - Nico Steffen (Review of International Economics, 2021)
This paper analyzes environmental concerns by a government in a setting of rent-extracting strategic trade policy with endogenous firm investment into production technologies. The simple analysis reinforces the importance of investment incentives caused by tariffs in general and shows that the resulting implications for the optimal tariff decision can be completely different between traditional tariff considerations and an environmentally conscious government. We show that an importing country in a dynamic setting with endogenous firm technology choices prefers to impose discriminatory tariffs both ex post and ex ante when emissions matter, while—as previously found in the literature—a commitment to uniform tariffs is optimally chosen when environmental concerns do not play a role.
Keywords: 330